Transport and health issues. - (:unkn) unknown (MetaGIS Infosysteme, 2011)
The series contains 10 articles: - Lars Bo Andersen and Ashley R Cooper. Commuter cycling and health - Martin Eder. The health benefit of cycling - Health Economic Assessment Tool (HEAT) for cycling. - Robert Pressl and Karl Reiter. Long term effects of the Transfer of Physical Activity into Everyday s Routine Programme in Graz, Austria. - Johansson, M., Raustorp, A. , Mårtensson, F. , Boldemann, C. , Sternudd, C. & Kylin, M. Attitudinal antecedents of children's sustainable every day mobility. - Marco Hüttenmoser. Road traffic threatens child development. We need a fundamental change of perspective. - Dr Nazan Kocak, Prof Tom Rye and Dr Ela Babalik-Sutcliffe. Prospects for changing the built environment to encourage more physical activity:a comparison of the UK and Turkey. - Helmut Schad, Roger Sonderegger and Timo Ohnmacht. Active travel and health A challenge for transport planning and urban planning. - Thomas Budde Christensen and Tyge Kjær. Planning for sustainable transport: The case of Copenhagen. - Davies, N.J., Lumsdon, L.M., Weston, R. Health Motivations for Recreational Walking. - Herbert Brüning. Noise action plan the strategic approach to advance sustainable transport. The example of Quiet Norderstedt. Worth living.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsmittelwahl; Mobilität; Gesundheit; Fahrradbenutzung; Mobilitätsverhalten; Gesundheitsförderung; Fahrradnutzung; Lärmschutz